катет1 = а
катет2 = а+1
гипотенуза в квадрате= катет1 в квадрате+катет2 в квадрате
25= а в квадрате + а в квадрате +2а +1
2 х а в квадрате + 2а -24=0
а = (-2 +_(плюс, минус) корень(4+ (4 х 2 х 24)) / 2 х 2
а = (-2 +- 14 )/ 4
а = 3 - катет1
3+1=4 - катет2
Прлощадь = (катет1 х катет2) / 2 = 3х4/2=6
катет1 = а
катет2 = а+1
гипотенуза в квадрате= катет1 в квадрате+катет2 в квадрате
25= а в квадрате + а в квадрате +2а +1
2 х а в квадрате + 2а -24=0
а = (-2 +_(плюс, минус) корень(4+ (4 х 2 х 24)) / 2 х 2
а = (-2 +- 14 )/ 4
а = 3 - катет1
3+1=4 - катет2
Прлощадь = (катет1 х катет2) / 2 = 3х4/2=6